Characterization of three neutral proteases of Spirometra mansoni plerocercoid - 공윤; Chung, Y.B.; Cho, S.Y.; Choi, S.H.; Kang, S.Y. (1994)
In the pathogenesis of sparganosis, proteases have been considered to play important roles in tissue migration and parasite feeding. Several bands of proteolysis were observed when crude extracts of Spirometra mansoni plerocercoid (sparganum) were examined using gelatin substrate gel at neutral pH, of which two proteases of 198 and 104 kDa were purified by two chromatographic steps, and a 36 kDa protease was purified by gelatin-affinity and DEAE-anion exchange chromatography. All the purified proteases exhibited optimal activity at pH 7？5 and 01 M TRIS-HCL.Proteolytic activities at 198 and 104 kDa were inhibited specifically by serine protease inhibitors, and 4-(amidinophenyl)methansulfonyl fluoride (APMSF, 0？5 mM) and N-α-p-tosyl-L-lysine chloromethyl ketone (TLCK, 1 mM), which strongly suggested that these two proteases were trypsin-like proteases. The activity of the 36 kDa protease was inhibited by N-tosyl-L-phenylalanine chloromethyl ketone (TPCK, 1 mM) and chymostatin (0？1 mM), and was potentiated in 10 mM Ca